A Functional Variant rs3093023 in CCR6 Is Associated With IgA Nephropathy by Regulating Th17 Cells in a North Han Chinese Population - Zhang, Yue-miao; Liu, Xing-zi; Zhou, Xu-jie; Liu, Li-jun; Shi, Su-fang; Hou, Ping; Lv, Ji-cheng; Zhang, Hong (Frontiers in Immunology, 2021)
C-C chemokine receptor 6 (CCR6) is a susceptibility gene of various immune-related diseases, which was suggested to be shared with IgA nephropathy (IgAN). Here, we were to identify the functional variants. First, we analyzed the associations of CCR6 common and rare variants detected by multi-platform chips with IgAN susceptibility using imputation, and identified 68 significantly associated common variants located in the regulatory region. Among them rs3093023 showed both statistical significance (rs3093023-A, odds ratio [OR]=1.15, P=2.00×10-2) and expression quantitative trait loci (eQTL) effect (P=1.45×10-3). It was independently replicated (rs3093023-A, OR=1.18, P=5.56×10-3) and the association was reinforced in meta-analysis (rs3093023-A, OR=1.17, P=6.14×10-7). Although rs3093023 was in strong linkage disequilibrium with the reported CCR6 functional variant dinucleotide polymorphism, CCR6DNP, the alleles of rs3093023 (G>A) rather than of CCR6DNP were shown differential nuclear protein binding effect by electrophoretic mobility shift assay. The RegulomeDB and JASPAR databases predicted Pou2f1 as the potential transcription factor, which was negatively associated with CCR6 mRNA (r=-0.60, P=3.94×10-9). At mRNA level, the eQTL effect of CCR6 was validated (P=4.39×10-2), and CCR6 was positive associated with CCR4 and IL-17A expression rather than with CXCR3 and IFNG. At protein level, a higher CCR6+ cell ratio was observed in a risk allele dose-dependent manner in lymphocytes (P=3.57×10-2), CD3+ T cells (P=4.54×10-2), and CD4+ T cells (P=1.32×10-2), but not in CD8+ T cells. Clinical-pathological analysis showed that rs3093023 risk allele was significantly associated with diastolic blood pressure, serum creatinine, and high ratio of tubular atrophy/interstitial fibrosis. Overall, the rs3093023 was prioritized as the function variant in CCR6 which may contribute to IgAN susceptibility by regulating Th17 cells.